FILOSOFI ZAT DAN MATERI MENURUT JABIR BIN HAYYAN (Aspek Kimiawi Dari Studi Filosofis terhadap Naskah Mukhtâr Rasâ`il ) - Edy Chandra (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2012)
This study used qualitative research method includes a study of literature, analysis descriptive method, historical and philosophical approach by considering substantial and functional relation between information and opinion from Jabir Ibn Hayyan’s manuscripts, ‘Mukhtâr Rasâ’il vol. 1 (collected by Paul Kraus, 1935). Even though he was influenced by mysticism, Jabir categorized as a pioneer of modern chemistry knowledge with empirical principle and scientific method base on experiment, contrary to the development was inclined of speculative rational at the time, mixing with Greek mysticism. His concept of atom is more advanced than Democritus atomism, parallel to Dalton’s atomic theory. His concept of Mizan mixing mysticism influence and cosmology, compounding quantitative and qualitative aspects of chemistry processes. Jabir used chemistry technique such as distillation, evaporation, sublimation, filtration, metal mixture, calcinations and so on.